2008
DOI: 10.1002/pmic.200701191
|View full text |Cite
|
Sign up to set email alerts
|

Extent of N‐terminal modifications in cytosolic proteins from eukaryotes

Abstract: Most proteins in all organisms undergo crucial N-terminal modifications involving N-terminal methionine excision, N-alpha-acetylation or N-myristoylation (N-Myr), or S-palmitoylation. We investigated the occurrence of these poorly annotated but essential modifications in proteomes, focusing on eukaryotes. Experimental data for the N-terminal sequences of animal, fungi, and archaeal proteins, were used to build dedicated predictive modules in a new software. In vitro N-Myr experiments were performed with both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
146
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(156 citation statements)
references
References 70 publications
9
146
0
Order By: Relevance
“…Acetylation is very common in proteins [estimated at >50% for eukaryotes (36)], but we could find no example of the capping motif presented herein. Even loop flanking W/W interactions are rare; to our knowledge, there is only one example in a protein (7).…”
Section: Discussionmentioning
confidence: 59%
“…Acetylation is very common in proteins [estimated at >50% for eukaryotes (36)], but we could find no example of the capping motif presented herein. Even loop flanking W/W interactions are rare; to our knowledge, there is only one example in a protein (7).…”
Section: Discussionmentioning
confidence: 59%
“…A recent study revealed that 84% of human proteins undergo NH 2 -terminal acetylation (3). Most proteins lose the NH 2 -terminal methionine by cleavage and are subsequently acetylated (29). When proteins undergo proteolysis, the NH 2 -terminal residue along with its acetyl adduct is released and circulates freely.…”
Section: Discussionmentioning
confidence: 99%
“…Another common mode of protein modification is N ␣ -acetylation, which has been estimated to occur in 30% or more of the proteins within eukaryotic cells (33,35,36). Although the sequence determinants for N ␣ -acetylation are not well defined, evidence does indicate that the penultimate residue is important (33,35,36).…”
Section: Post-translational Processing Of the N-terminal End Of Ts-mentioning
confidence: 99%
“…Two primary modifications are known to occur at the N termini of proteins. Cleavage of the initiator Met, which results in the penultimate amino acid becoming the N-terminal residue in the mature polypeptide, is commonly observed (31)(32)(33). Several studies have shown that polypeptides with small side chains at the penultimate position (i.e.…”
Section: Post-translational Processing Of the N-terminal End Of Ts-mentioning
confidence: 99%